2020
DOI: 10.3390/ma13071669
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Microcapsules Coating and the Study of Their Bionic Anti-Fouling Performance

Abstract: With the increasing demands to better the marine environment, environmentally friendly anti-fouling coatings have attracted attention from society. Adding hydrolyzable microcapsules without toxin to paints is a very useful and safe method to get bionic anti-fouling coatings with a micro-nano surface structure. Based on this trend, a form of environment-friendly microcapsules were prepared through mini-emulsion polymerization. The target microcapsules had a poly(urea-formaldehyde) (PUF) shell and a mixed core o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Li et al [ 75 ] prepared a form of environment-friendly microcapsules through mini-emulsion polymerization as show in Figure 17 . They used zinc acrylate resin to wrap the synthetic microcapsules into a coating, and investigated the slow release efficiency and antifouling effect of the coating.…”
Section: Marine Antifouling Coatingmentioning
confidence: 99%
“…Li et al [ 75 ] prepared a form of environment-friendly microcapsules through mini-emulsion polymerization as show in Figure 17 . They used zinc acrylate resin to wrap the synthetic microcapsules into a coating, and investigated the slow release efficiency and antifouling effect of the coating.…”
Section: Marine Antifouling Coatingmentioning
confidence: 99%
“…Three kinds of gloss were measured at incident angles of 20 • , 60 • and 85 • . The higher the value was, the higher the gloss was [31,32], which is shown in Table 2. It can be concluded that for microcapsules with the same core-wall ratio and incident angle, the gloss of the coating film without the microcapsules was the best, and then the gloss of the coating decreased with an increase of the mass fraction of the microcapsules.…”
Section: Effect Of Different Core To Wall Ratio On the Glossmentioning
confidence: 99%
“…It is important to prepare microcapsules with stable encapsulation and release efficiency using suitable methods [ 10 ]. Commonly used microcapsule preparation methods include the complex coacervation method, the ionic gel method, the microemulsion polymerization method, the layer-by-layer assembly method, and the air-suspension method [ 11 , 12 , 13 , 14 , 15 ]. Although many preparation technologies are suitable for microcapsules, no encapsulation method is suitable for all situations.…”
Section: Introductionmentioning
confidence: 99%